2021
DOI: 10.1002/htj.22056
|View full text |Cite
|
Sign up to set email alerts
|

Computational single phase comparative study of inclined MHD in a Powell–Eyring nanofluid

Abstract: In this study, the heat transfer and entropy of transient non‐Newtonian Powell–Eyring nanofluid flow is studied. The nanofluid flows over a stretched flat surface, moving nonuniformly. The flow and heat transfer properties are analyzed subject to a convective heated slippery surface. This study also examined the thermal radiation, nanoparticle shapes, inclined magnetic field (B), and joule heating. The governing equations of flow are formulated in partial differential equations (PDEs). A numerical technique ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Al-Farhany et al [19] and Al-Farhany et al [20] explored the 2D flow of nanofluid with fin effects in the cavity. Jamshed et al [21] reported MHD Eyring-Powell nanofluid using SWNT past an inclined sheet. Nowadays, the fluid flow over a wedge surface has paid remarkable attention due to its vast applications in industries and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Farhany et al [19] and Al-Farhany et al [20] explored the 2D flow of nanofluid with fin effects in the cavity. Jamshed et al [21] reported MHD Eyring-Powell nanofluid using SWNT past an inclined sheet. Nowadays, the fluid flow over a wedge surface has paid remarkable attention due to its vast applications in industries and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The cavity-based 2D (two-dimensional) flow of nanoliquid with fin effects was planned by Al-Farhany et al [ 19 , 20 ]. The Eyring–Powell nanoliquid exploitation using SWNTover an inclined plate was developed by Jamshed et al [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a novel subject that is utilized in the aerospace industry. In addition, MHD is one of the procedures that can influence heat and flow on a stretching surface 1–21 . Titanium dioxide, too known as titanium (IV) oxide or titania, is the noted oxide of titanium, chemical equation TiO 2 .…”
Section: Introductionmentioning
confidence: 99%